2005
DOI: 10.3139/146.018080
|View full text |Cite
|
Sign up to set email alerts
|

A unified equation for the viscosity of pure liquid metals

Abstract: A unified equation for the viscosity of pure liquid metalsThe following unified equation has been elaborated in the present paper, to describe the viscosity of all liquid metals as a function of temperature:i being the dynamic viscosity, atomic mass, molar volume and melting point of the given metal i, and T is temperature. The above equation was tested on 101 measured points of 15 selected liquid metals, and the average values of the generally valid parameters were found as: A = (1.80 AE 0.39) · 10 -8 (J/Kmol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
84
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 114 publications
(99 citation statements)
references
References 28 publications
1
84
0
Order By: Relevance
“…(9) in non-reduced units. 60 This expression was shown to work well for 18 metals at ambient pressure. 60 Equation (10) is qualitatively different by having (T F /T ) 1/2 instead of T F /T in the exponential.…”
mentioning
confidence: 92%
See 2 more Smart Citations
“…(9) in non-reduced units. 60 This expression was shown to work well for 18 metals at ambient pressure. 60 Equation (10) is qualitatively different by having (T F /T ) 1/2 instead of T F /T in the exponential.…”
mentioning
confidence: 92%
“…60 This expression was shown to work well for 18 metals at ambient pressure. 60 Equation (10) is qualitatively different by having (T F /T ) 1/2 instead of T F /T in the exponential. The new viscosity equation represents data well in the region of the phase diagram studied by Kaptay and others, as well as at much higher temperatures.…”
mentioning
confidence: 92%
See 1 more Smart Citation
“…is justified by experimental data mainly at the melting point of liquids [19]. In the present study, we have used the ultrasonic Interferometer (Mittal Enterprises Make) for the observation of ultrasonic velocity (C) and knowing the frequency we can find out various parameters such as adiabatic compressibilitysurface tension , viscosity.…”
Section: Some Formulae Of the Parameters To Be Calculated Arementioning
confidence: 99%
“…The calculations of viscosity of cholestryl oleyl carbonate is done according to the statistical calculations [19,20]. statistical mechanics provides a solid scientific basis to calculate viscosity of liquids.One of the useful approximate solutions of the statistical mechanical approach is due to Chapman [20], who characterized the force between the atoms in liquids by a distance parameter (the Goldschmidt atomic diameter, di) and a semi-empirical energy parameter (ei).Chapman showed that the reduced experimental viscosity data can be plotted as a function of the reduced temperature using a unique curve for all liquids.…”
Section: IImentioning
confidence: 99%